Strategic Planning for Taiwanese Industrial Tourism Parks Themed on Local Characteristic Industries - TAI, Hung-I; LIU, Li-Wei; YANG, Lung-Shih; HSIEH, Chi-Chiang (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.v14.4(68).06, 2023)
This study examined Puli Industrial Micro-Park for a case study. In line with Nantou County’s efforts to promote itself as a tourism capital, the park was designed as an industrial cluster that is themed on industrial tourism. This study explored the planning and operation of Puli Industrial Micro-Park and conducted in-depth interviews to understand its development history and implementation performance. Finally, it summarized the key factors that contributed to the successful development of industrial tourism parks with local characteristics, namely self-liquidating capability, land price, park development characteristics, comprehensive park planning, and park cooperation with nearby industries.